2016
DOI: 10.1038/srep37935
|View full text |Cite
|
Sign up to set email alerts
|

Trans-translation is essential in the human pathogen Legionella pneumophila

Abstract: Trans-translation is a ubiquitous bacterial mechanism for ribosome rescue in the event of translation stalling. Although trans-translation is not essential in several bacterial species, it has been found essential for viability or virulence in a wide range of pathogens. We describe here that trans-translation is essential in the human pathogen Legionella pneumophila, the etiologic agent of Legionnaire’s disease (LD), a severe form of nosocomial and community-acquired pneumonia. The ssrA gene coding for tmRNA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 68 publications
(81 reference statements)
7
31
0
Order By: Relevance
“…Trans-translation is essential in species lacking alternative mechanisms (16). In agreement with these observations, alternative ribosome-rescue systems are absent in members of the Legionellaceae genus and we indeed found that trans-translation is essential for L. pneumophila growth and infection of its cellular host (32). In L. pneumophila, expressing the alternate rescue factor ArfA from E. coli can compensate for the loss of transtranslation activity indicating that the ribosome-dissociating activity of the trans-translation system is the sole function required for viability (32).…”
Section: Introductionsupporting
confidence: 89%
See 4 more Smart Citations
“…Trans-translation is essential in species lacking alternative mechanisms (16). In agreement with these observations, alternative ribosome-rescue systems are absent in members of the Legionellaceae genus and we indeed found that trans-translation is essential for L. pneumophila growth and infection of its cellular host (32). In L. pneumophila, expressing the alternate rescue factor ArfA from E. coli can compensate for the loss of transtranslation activity indicating that the ribosome-dissociating activity of the trans-translation system is the sole function required for viability (32).…”
Section: Introductionsupporting
confidence: 89%
“…On L. pneumophila, several results led us to question the link between inhibition of transtranslation and antibiotic activity. First, no synergy was found between KKL-35 and ribosome-targeting antibiotics, whereas we previously found that a reduction in tmRNA levels led to an increased susceptibility of L. pneumophila to such antibiotics (32). Second, L. pneumophila cells treated with KKL-35 did not display the filamentation phenotype observed in cells lacking tmRNA.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations